2017
DOI: 10.1111/jphd.12227
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Futures: Engaging the oral health community in childhood obesity prevention – Conference summary and recommendations

Abstract: Childhood obesity is a major public health problem. An association between obesity and dental caries, the most prevalent disease of childhood, has been identified. One explanation for the association is that consumption of sugarsweetened beverages and frequent snacking on carbohydrate-rich foods are common risk factors for development of both obesity and caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The first National Dietary Survey, which was conducted in 2008-2009, indicated that 61% of the population consumed more than >10% free sugars for their total energy intake [22]. It is worth mentioning that this high pattern of sugar consumption is contrary to the recommendation of the WHO, which states that the intake of free sugars for the prevention and control of unhealthy weight gain and dental caries in adults and children, should be reduced to less than 10% of the total number of calories from the diet [4]. A further reduction in the intake of free sugars to <5% of energy has been suggested [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first National Dietary Survey, which was conducted in 2008-2009, indicated that 61% of the population consumed more than >10% free sugars for their total energy intake [22]. It is worth mentioning that this high pattern of sugar consumption is contrary to the recommendation of the WHO, which states that the intake of free sugars for the prevention and control of unhealthy weight gain and dental caries in adults and children, should be reduced to less than 10% of the total number of calories from the diet [4]. A further reduction in the intake of free sugars to <5% of energy has been suggested [23].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, the diseases resulting from it and dental caries have in diet an important etiologic component in common, since both the amount and frequency of sucrose are important factors involved in their etiology [4]. According to the WHO, increased sugar intake may be related to unhealthy diet and the increase in the risk of various diseases, such as overweight, obesity, dental caries and other non-communicable chronic diseases [5].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated rates of childhood dental caries and obesity call for multi-tiered approaches, including prevention efforts in clinical settings [Garcia et al, 2017]. Chronic illnesses have been targeted in the PED, including screening, brief interventions and referrals [Chandler et al, 2015;Haber et al, 2015;Herndon et al, 2017;Vaughn et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…Advocates support primary prevention of these chronic diseases in dental settings [Yuan et al, 2012] with family-centered and tailored techniques for limiting sugar consumption and improving diet healthiness. Dental clinics offer opportune locations in the health system to screen for obesity, promote healthy behaviors, and connect families with specialized care [Garcia et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation